On the value of advanced information about delayed rewards - Alejandro Macías; Armando Machado; Marco Vasconcelos (Animal Cognition)
Abstract In a variety of laboratory preparations, several animal species prefer signaled over unsignaled outcomes. Here we examine whether pigeons prefer options that signal the delay to reward over options that do not and how this preference changes with the ratio of the delays. We offered pigeons repeated choices between two alternatives leading to a short or a long delay to reward. For one alternative (informative), the short and long delays were reliably signaled by different stimuli (e.g., S S for short delays, S L for long delays). For the other (non-informative), the delays were not reliably signaled by the stimuli presented (S 1 and S 2). Across conditions, we varied the durations of the short and long delays, hence their ratio, while keeping the average delay to reward constant. Pigeons preferred the informative over the non-informative option and this preference became stronger as the ratio of the long to the short delay increased. A modified version of the Δ–Σ hypothesis (González et al., J Exp Anal Behav 113(3):591–608. https://doi.org/10.1002/jeab.595 , 2020a) incorporating a contrast-like process between the immediacies to reward signaled by each stimulus accounted well for our findings. Functionally, we argue that a preference for signaled delays hinges on the potential instrumental advantage typically conveyed by information.